1998
DOI: 10.1007/s100169900190
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for the Study of Lower Extremity Chronic Venous Disease: Lessons Learned and Future Needs

Abstract: The purpose of this review is to define animal models of chronic venous disease and to demonstrate how animal studies can impact our understanding and treatment of this disorder. To this end an extensive literature search was conducted highlighting potential animal models of chronic lower extremity venous disease. Scientific investigations using animals to study particular aspects of this disease are also reviewed. This review was conducted by members of the Committee on Research of the American Venous Forum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…13 Previous attempts for the treatment of chronic venous insufficiency with natural tissue, that did not utilize tissue-engineering techniques, including valve repair, transplantation of autologous valves or cryopreserved vein segments were encouraging. 4,14,15 In this current project valved venous conduits were grown in a bioreactor using a decellularised allogeneic ovine jugular vein as donor matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Previous attempts for the treatment of chronic venous insufficiency with natural tissue, that did not utilize tissue-engineering techniques, including valve repair, transplantation of autologous valves or cryopreserved vein segments were encouraging. 4,14,15 In this current project valved venous conduits were grown in a bioreactor using a decellularised allogeneic ovine jugular vein as donor matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, implantation of venous segments into the external jugular of sheep provides an appropriate option for the in vivo evaluation of TE grafts, but it does not serve as a model for the study of lower limb chronic venous insufficiency since venous pressures are not elevated during observation. 14 TE venous valved conduits were successfully integrated into the host with minor inflammatory reactions (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…The next section of this review addresses the use of animal models for the study of chronic venous disease, specifically the inflammatory processes that are involved in the pathogenesis of chronic venous insufficiency. It is recognized that clinical advancement related to the treatment of this disease has been hindered by a lack of animal models (13). Almost twenty years ago, it was demonstrated that microvascular abnormalities similar to those that precede lipodermatosclerosis and venous ulceration in humans could be produced in a canine hindlimb model with venous hypertension (6).…”
Section: Experimental Models To Investigate Inflammatory Processes Inmentioning
confidence: 99%
“…Almost twenty years ago, it was demonstrated that microvascular abnormalities similar to those that precede lipodermatosclerosis and venous ulceration in humans could be produced in a canine hindlimb model with venous hypertension (6). Although such large animal models have proved to be invaluable as a means to evaluate surgical methods for correcting venous hypertension and insufficiency, they have generally been considered deficient for studying pathogenetic mechanisms of venous disease because the chronic skin abnormalities observed in humans do not occur (13). While it is desirable to have an animal model of CVI that reproduces every aspect of the human condition, it must be recognized that models that mimic the early characteristics of microvascular changes associated with venous disease can be useful in understanding the pathophysiologic steps in the development of venous ulceration and in evaluating potential treatments.…”
Section: Experimental Models To Investigate Inflammatory Processes Inmentioning
confidence: 99%